O9 Is HIV and blood borne virus testing acceptable and indicated in psychiatric settings?. (23rd May 2012) - Sanger, C; Hayward, J; Patel, G; Poots, A; Howe, C; Green, J
Abstract : Objective: Studies in North America and Europe indicate that the prevalence of blood borne viruses (BBVs) are elevated in individuals with severe mental illness. No comparable data exists for the UK. We introduced the routine offer of testing for HIV, Hepatitis B and C into an inpatient psychiatric unit, where the local diagnosed HIV prevalence is 7.29/1000. Method: Psychiatric inpatients were approached at one central London hospital site, between April 2011 and February 2012 and offered routine BBV testing. Results: Of the first 100 patients offered a test 83% of patients approached were assessed to have mental capacity to provide informed consent for testing. 69% of patients offered BBV testing, accepted. The prevalence of HIV was found to be 3%. One individual was newly diagnosed with HIV and transferred to specialist care. Overall, 18% of patients tested were found to have a newly diagnosed or previous infection with a BBV. Conclusion: It is acceptable to patients to be offered routine BBV screening in a psychiatric setting and the majority have capacity to consent; uptake rate is comparable to that seen in GUM clinics. HIV prevalence rate was found to be over four times higher than that of the local population. Given the elevated prevalence rates in psychiatric patients, there is a strong case for the wider introduction of routine testing in mental health settings. There is a need to systematically ascertain rates of infection in mental health patients across a range of geographical areas since the prevalence of BBVs appears to be higher than that in the local population.